Morphofunctional state and interrelations of cardiovascular and autonomic indicators in athletes of different game sports - Yaroslav Svyshch; Oksana Guzii; Sergey Kalmykov; Yuliya Kalmykova; Oleksandr Romanchuk (Physical Rehabilitation and Recreational Health Technologies, 2026)
Purpose. Accessible resting and functional-test indices are widely used to monitor athletes, yet whether their interrelations are independent of body size and differ by autonomic tone across game sports is unknown. We compared morphofunctional, cardiovascular and autonomic indicators of athletes of five game sports and tested the interrelations of these indicators, including adjustment for body size and stratification by autonomic-regulation type. Materials & Methods. In a cross-sectional design, 206 qualified male athletes of five game sports (water polo, basketball, volleyball, handball, football) underwent anthropometry, spirometry, handgrip dynamometry, resting blood pressure measurement and the Martinet–Kushelevsky functional test (20 squats in 30 s). Classical indices (body mass index, vital index, Pignet, Robinson, Kerdo, Baevsky adaptation potential) and cardiovascular reactivity/recovery indices were computed. Kruskal–Wallis tests with epsilon-squared effect size, Spearman correlations with Benjamini–Hochberg correction, partial correlations adjusted for age and body mass, and separate correlations within sympathico- and parasympathicotonic subgroups (Kerdo sign) were applied; a sensitivity power analysis was performed. Results. Groups differed in most indicators, mostly with large effects. Of 300 pairs, 155 associations were significant (FDR